RESPON TANAMAN SAWI HIJAU (Brassica juncea L.) TERHADAP PUPUK KOMPOS DAN PUPUK UREA - Duka, Ngailu Beko; Hamzah, Amir; Sutoyo, Sutoyo (Universitas Tribhuwana Tunggadewi, 2017)
Mustard green (Brassica juncea L.) is one of the leafy vegetable horticulture commodities that are favored by the community because it tastes good (Pardosi et al., 2014). The area of harvest of mustard plant production in 2011 was 376 ha with a yield of 3,410 tons with an average yield of 9.07 tons of ha-1 for 2012, while the average is still very low when compared to the national production scale that is between 9.44 Ton ha-1 (Pardosi at al., 2014). One important factor in the cultivation that supports the success of the production of mustard plants is fertilization. The efficiency of N fertilization in mustard plants is low, ranging from 30-40%. This study aims to determine the response of green mustard plants to the application of compost fertilizer from municipal waste and urea fertilizer to the growth and yield of green mustard plants. The tool used for this research is hoe, arit, gembor, meter, scales, bucket, camera, stationery, paper label, sieve, polybag with volume 10 kg, calculator and handsprayer. The materials used in this research are green mustard seed, compost fertilizer and urea fertilizer. The study used Factorial Randomized Block Design (RAK) consisting of two factors. The first factor is the dosage of compost fertilizer from municipal wastes with 5 levels ie (1) No Compost, (2) Compost 20 ton / ha, (3) Compost 40 ton / ha, (4) Compost 60 ton / ha, (5) Compost 80 tons / ha. The second factor was the dose of urea fertilizer (N) with 5 levels: (1) without Urea, (2) 100 Urea kg / ha, (3) 150 Urea kg / ha, (4) 200 Urea kg / ha and (5 ) 250 Urea kg / ha. Both factors yielded 25 treatment combinations, each repeated 3 times. Observation variables consist of plant height, Number of leaves, Leaf Area, Wet Weight and Fresh Weight of Plant. The data obtained were analyzed using variance (ANOVA). Conclusion of research (1) There is interaction between compost fertilizer and urea fertilizer on observation of leaf number and leaf area, (2) Compost fertilizer giving effect to the height of mustard plant, leaf area, leaf number and wet weight of plant, (3) Of plant height, number of leaves, leaf area and wet weight of the plant. Sawi (Brassica juncea L.) merupakan salah satu komoditas hortikultura sayuran daun yang banyak digemari oleh masyarakat karena rasanya enak, mudah didapat serta proses budidayanya tidak terlalu sulit Salah satu faktor penting dalam budidaya yang menunjang keberhasilan produksi tanaman sawi adalah pemupukan. Efisiensi pemupukan N pada tanaman sawi tergolong rendah, berkisar antara 30-40%. Penelitian ini bertujuan untuk mengetahaui respon tanaman sawi hijau terhadap pemberian pupuk kompos dari limbah kota dan pupuk urea terhadap pertumbuhan dan hasil tanaman sawi hijau. Alat yang digunakan untuk penelitian ini adalah cangkul, arit, gembor, meteran, timbangan, ember, kamera, alat tulis, kertas label, ayakan, polybag dengan volume 10 kg, kalkulator dan handsprayer. Bahan yang digunakan dalam penelitian ini adalah benih sawi hijau, pupuk kompos dan pupuk urea. Penelitian ini menggunakan Rancangan Acak Kelompok (RAK) faktorial yang terdiri dari dua faktor. Faktor pertama yaitu dosis pemberian pupuk kompos dari limbah kota dengan 5 taraf yaitu (1) Tanpa Kompos, (2) Kompos 20 ton/ha, (3) Kompos 40 ton/ha, (4) Kompos 60 ton/ha, (5) Kompos 80 ton/ha. Faktor kedua dosis pemberian pupuk urea (N) dengan 5 taraf yang yaitu : (1) Tanpa Urea, (2) 100 Urea kg/ha, (3) 150 Urea kg/ha, (4) 200 Urea kg/ha dan (5) 250 Urea kg/ha. Kedua faktor menghasilkan 25 kombinasi perlakuan, masing-masing diulang 3 kali. Variabel pengamatan terdiri dari tinggi tanaman, Jumlah daun, Luas Daun, Bobot basah tanaman dan Bobot Segar Tanaman. Data yang diperoleh dianalisis dengan menggunakan sidik ragam (ANOVA). Kesimpulan penelitian yaitu (1) Terjadi interaksi antara pupuk kompos dengan pupuk urea pada pengamatan jumlah daun dan luas daun, (2) Pemberian pupuk kompos berpengaruh terhadap tinggi tanaman sawi, luas daun, jumlah daun dan berat basah tanaman, (3) Pemberian pupuk urea berpengaruh terhadap tinggi tanaman, jumlah daun, luas daun dan berat basah tanaman.